Promoting community health during COVID-19: a service-learning experience in Selangor - Chen, Xin Wee; Mat Ruzlin, Aimi Nadira; Mohd Yunus, Raudah; Samsudin, Ely Zarina (Faculty of Medicine, 2025)
Given the prolonged movement restrictions that have led to sudden lifestyle changes and rising mental health concerns, innovative health promotion approaches are inevitable. ‘Health Fest UiTM’ was a virtual health promotion program conducted to address some of the overarching issues facing our communities during the COVID-19 pandemic. This paper aims to describe the implementation of ‘Health Fest UiTM’ as a public health service-learning tool with a community- based teaching and learning approach The ‘Health Fest UiTM’ project was organized by the Department of Public Health Medicine from the end of July to early August 2021. Four key themes were identified based on a community health needs assessment. They included: i) COVID-19 immunization, ii) mental health awareness, iii) physical activity and healthy diet during the pandemic, and iv) domestic violence awareness. Various activities were conducted using different social networking sites (SNSs) and anonymity was ensured to encourage greater participation and minimize stigmatization In total, 214 fourthyear undergraduate medical students were involved in this service-learning program. Five virtual live events displayed favorable SNSs engagement metrics that ranged from 200 to 1000 participants and the total number of views and shares for the educational materials posted on SNSs exceeded 35,000. The COVID-19 pandemic has accelerated the integration of digital technology into the performance and delivery of servicelearning in providing access to health information and education as well as facilitating community engagement through virtual platforms.